Effect of dissolved hydrogen on Schottky barrier height of Fe-Cr alloy heterojunction - Berahim, A N; Zaharudin, M Z; Ani, Mohd Hanafi; Arifin, S K (IOP Publishing, 2018)
The presence of water vapour at high temperature oxidation has certain effects on ferritic alloy in comparison to dry environment. It is hypothesized that at high temperature; water vapour provides hydrogen, which will dissolve into ferritic alloy substrate and altering their electronic state at the metal-oxide interface. This work aimed to clarify the change in electronic state of metal-oxide heterojunction with the presence of hydrogen/water vapour. In this study, the Schottky Barrier (SB) was created by sputtering Cr2O3 onto prepared samples using RF Magnetron sputtering machine. The existence of Fe/Cr2O3 junction was characterized by using XRD. The surfaces were observed by using Optical Microscope (OM) and Scanning Electron Microscope (SEM). The samples were then exposed in dry and humid condition at temperature of 473 K and 1073 K. In dry condition, 100% Ar is flown inside the furnace, while in wet condition mixture of 95% Ar and 5% H was used. I-V measurement of the junction was done to determine the Schottky Barrier Height(SBH) of the samples in the corresponding ambient. The results show that in Fe/Cr2O3 junction, with presence of hydrogen at temperature 473 K; the SBH was reduced by the scale factor of 1.054 and at 1073 K in wet ambient by factor of 1.068. Meanwhile, in Fe-Cr/Cr2O3 junction with presence of hydrogen, the value of SBH was increased by scale factor of 1.068 at temperature 473 K while at 1073 K, the SBH also increased by factor of 1.009.